2012
DOI: 10.1007/s12041-012-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide analysis of intronic microRNAs in rice and Arabidopsis

Abstract: MicroRNAs (miRNAs) are potent regulators of gene transcription and posttranscriptional processes. The majority of miRNAs are localized within intronic regions of protein-coding genes (host genes) and have diverse functions in regulating important cellular processes in animals. To date, few plant intronic miRNAs have been studied functionally. Here we report a comprehensive computational analysis to characterize intronic miRNAs in rice and Arabidopsis. RT-PCR analysis confirmed that the identified intronic miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…These detailed analyses on genomic annotation of miRNAs in grapevine can serve as a reference for future research on evolution. We found that the percentage of intragenic miRNAs in grapevine was approximately 0.9 times higher than in rice (23.0 vs. 25.4%) and 0.43 times higher than in A. thaliana (23.0 vs. 52.9%) (Yang et al, 2012). We also found that the proportion of intronic miRNAs in grapevine was approximately 1.1 times higher than in A. thaliana and 2.8 times higher than in rice (Table 3).…”
Section: Analysis Of Intergenic and Intragenic (Intronic Exonic) Micmentioning
confidence: 72%
“…These detailed analyses on genomic annotation of miRNAs in grapevine can serve as a reference for future research on evolution. We found that the percentage of intragenic miRNAs in grapevine was approximately 0.9 times higher than in rice (23.0 vs. 25.4%) and 0.43 times higher than in A. thaliana (23.0 vs. 52.9%) (Yang et al, 2012). We also found that the proportion of intronic miRNAs in grapevine was approximately 1.1 times higher than in A. thaliana and 2.8 times higher than in rice (Table 3).…”
Section: Analysis Of Intergenic and Intragenic (Intronic Exonic) Micmentioning
confidence: 72%
“…A number of miRNA genes in plants reside within an intron of protein coding genes and are coexpressed and processed with the host protein-coding gene Yan et al, 2012;Yang et al, 2012a). AS of primary transcripts due to IR and exon skipping of several plant miRNAs has been reported (Aukerman and Sakai, 2003;Kurihara and Watanabe, 2004;Hirsch et al, 2006;Szarzynska et al, 2009).…”
Section: Coupling Of As To Mrna Stability Through Nmdmentioning
confidence: 99%
“…Dicerlike1 (DCL1), a key endonuclease in biogenesis of miRNA from primiRNA (Rogers and Chen, 2013b), has 20 exons and contains an MBS for miR162 that is interrupted by intron 12. AS in this intron generates four isoforms (DCL1-1 to DCL1-4), and one of these four isoform contains an MBS (Yang et al, 2012a). Hence, regulated AS of DCL1 pre-mRNAs would affect regulation of DCL1 protein levels.…”
Section: Coupling Of As To Mrna Stability Through Nmdmentioning
confidence: 99%
“…Introns of protein-coding genes, where MIR genes are hosted are referred to as mirtrons. Until date, they have been discovered in invertebrates and mammals (Berezikov et al 2007), and, more recently, in rice and Arabidopsis (Yang et al 2012).…”
Section: Discussionmentioning
confidence: 99%